TRIAGE TRAINING ON TABLETOP DISASTER EXERCISE (TDE) INCREASE THE ABILITY TO IDENTIFY VICTIMS OF FLOOD DISASTER IN ADOLESCENTS - Kusno Ferianto; Karyo, Karyo; Mohammad Fahrul Arifin; Hidayah Sahri , Novia (jfpublisher, 2025)
Introduction. The ability to identify flood victims in Indonesia is still low, therefore efforts to improve the ability to identify victims in adolescents must be improved. Triage training based on Tabletop Disaster Exercise (TDE) will make it easier for adolescents to understand disaster scenarios. This study aims to determine triage training on tabletop disaster exercise (TDE) to increase the ability to identify victims of flood disasters in adolescents. Method. The research design used in this study was a pre-experiment with a one-group pre-post test design. The population of 30 people was selected using a simple random sampling technique to obtain 28 respondents. Results and Analysis. The independent variable is Triage training and the dependent variable is the ability to identify disaster victims as measured using the chi-square test. The analysis in this study used the Chi-Square Test with a significance level of α = 0.05 and the processing was carried out using SPSS software version 26.0 for Windows, obtaining the Asymp Sig. Value. = 0.000. So p = 0.000 < 0.05 then H1 = accepted. Discussion. Based on this analysis meaning that there is a triage training on tabletop disaster exercise (TDE) to increase the ability to identify victims of flood disasters in adolescents.